Notários e registradores no tratamento consensual de conflitos - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Under the justification of effective access to justice, the State has given a new system to the treatment of conflicts, encouraging the use of the most suitable methods according to the presented reality. This paper focuses on the study of the role of notary and registry agents as conciliators and mediators, considering the permission granted by the National Council of Justice (CNJ). Society, guided by the idea that it is the State's responsibility to ensure the vast majority of its rights, has culturally attributed to the Judiciary the notion that justice will only be achieved when endorsed by the State- Judge, through a judgment of merit; embodying what proceduralists call the culture of litigation. In contrast, the State itself, aware that the Judiciary is not the only source for conflict resolution, regulates other forms of access, promoting the application of multiple available techniques, emphasizing the development of the Multi-Door Justice. Among the possibilities, Mediation and Conciliation have gained some ground. Notary and registry agents, in turn, have increasingly acted as a gateway to justice. This is contributed by the national legislator who, by editing various norms focused on the extrajudicialization of access to justice, contributes to enhancing the Multi-Door System in conflict resolution. Among these possibilities of action is the activity of these delegates as mediators and conciliators. Thus, the objective of this dissertation is to present a proposal that allows the effective implementation of mediation and conciliation by Notaries and Registrars as an effective tool for handling conflicts extrajudicially. The specific objectives are aligned with the necessary stages for the realization of the work and the proposed presentation, namely: analyzing the conflict in society and ensuring access to justice; identifying methods of conflict resolution in society; and pointing out notes on the notarial and registry activity, analyzing the legal permission for notary agents to act as mediators and conciliators.
Keywords: Conflito de interesse; Acesso à Justiça; Justiça Multiportas; Mediação e Conciliação; Notários e Registradores; Conflict of interest; Access to Justice; Multi-Door Justice; Mediation and Conciliation; Notaries and Registrars; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO